Sebagai Upaya Meningkatkan Pendapatan Masyarakat Desa Wonomerto Melakukan Budidaya Jamur Tiram Putih - Huda, Syamsul; Utami, Anisa Fitria; Mubarrok, Muhamad Raafi Al Hadi (Universitas Gajah Putih, Indonesia, 2023)
Indonesia, with a hot climate and high humidity, is an ideal place for the growth of various types of mushrooms. And also, cultivating oyster mushrooms is quite easy when compared to others. Apart from that, the main advantage of oyster mushroom cultivation is that it does not require extensive permits, has a long relatively short harvest of about one to three months, and oyster mushroom seeds are easy to obtain at an affordable price. In this research, the Participatory Action Research (PAR) method is used, which is a research approach that involves the active participation of people involved in the context being studied. It is hoped that with the cultivation of oyster mushrooms in Wonotirto Hamlet which continues to grow, the situation can change so that it can increase the income of local residents. With the development of oyster mushroom cultivation in Indonesia, especially Wonomerto Village, it is hoped that the number of oyster mushroom farmers or entrepreneurs can continue to increase so that oyster mushroom production can also increase.